A finite element based approach for fatigue life prediction of headed shear studs. (June 2019) - Mia, Md. Manik; Bhowmick, Anjan K.
Abstract: Steel shear studs in bridges are subjected to rapidly fluctuating stresses causing fatigue failure. Research on fatigue of shear studs mainly focused on tests. Both AASHTO and Canadian design curve for fatigue resistance of shear studs are based on the tests conducted in the mid1960s by Slutter and Fisher. This paper presents a finite element based approach using push-out specimen for fatigue life estimation of headed shear stud connectors. Both crack initiation and crack propagation life are estimated and an excellent correlation is found when compared against test results. In addition, since a significant amount of push-out tests data on headed shear studs are now available, this paper evaluates the fatigue design curves of different standards, with special focus given to evaluation of the value of constant amplitude fatigue limit (CAFL) given in the current AASHTO and Canadian code (CSA S6-14). The regression analysis also shows that the current fatigue curves in different codes can be used for shear studs as large as 31.8 mm. Thus, restriction of use of studs larger than 25 mm (1 in.) in different bridge codes (CSA S6, Eurocode 4, and AASHTO) can be waived.